Cellular and molecular introduction to brain development - Xiangning Jiang; Jeannette Nardelli (Neurobiology of Disease, 2016)
Advances in the study of brain development over the last decades, especially recent findings regarding the evolutionary expansion of the human neocortex, and large-scale analyses of the proteome/transcriptome in the human brain, have offered novel insights into the molecular mechanisms guiding neural maturation, and the pathophysiology of multiple forms of neurological disorders. As a preamble to reviews of this issue, we provide an overview of the cellular, molecular and genetic bases of brain development with an emphasis on the major mechanisms associated with landmarks of normal neural development in the embryonic stage and early postnatal life, including neural stem/progenitor cell proliferation, cortical neuronal migration, evolution and folding of the cerebral cortex, synaptogenesis and neural circuit development, gliogenesis and myelination. We will only briefly depict developmental disorders that result from perturbations of these cellular or molecular mechanisms, and the most common perinatal brain injuries that could disturb normal brain development.